A replacement name for Flavala Behounek, Han & Kononenko, 2012 (Lepidoptera: Noctuidae: Pantheinae) - Behounek, G.; Han, H.l.; Kononenko, V.s. (Zootaxa, 2016)
The genus name Flavala Behounek, Han & Kononenko, 2012 (homonym nov.) must be replaced by Mooreia nomen nov. because Flavala is preoccupied by Flavala Berio, 1966, the junior synonym of Thioptera Franclemont, 1950, the Nearctic Eustrotiinae genus (Lepidoptera, Noctuidae, Eustrortiinae). The name Mooreia is dedicated to Frederic Moore, the famous British lepidopterologist of the nineteenth century, the explorer of the Oriental fauna, described many Lepidoptera taxa including Acronycta flavala Moore, 1867.